SAMIRATA a Musical Art Composition Creative Percusion | SAMIRATA Sebuah Karya Komposisi Seni Karawitan Tabuh Kreasi - I Ketut Garwa; Kadek Angga Wahyu Pradana (Pusat Penerbitan LPPMPP ISI Denpasar, 2021)
Abstract The creation of this final percussion is starting to decrease, especially in Buleleng. In the past five (5) years, there has been no creative percussion in the form of a game pattern that focuses on the melodic processing approach, but the packaging or presentation of creative percussion works tends to use a rhythmic working approach. From the differences above, the stylist wants to create a more dynamic musical composition work. The medium expressed in this creative musical composition is the North Balinese style barungan gong kebyar (pacekan). From this, ideas emerged in the stylist to create a creative percussion composition entitled